Management of pleural infections. (3rd June 2018) - Ferreiro, Lucía; Porcel, José M.; Bielsa, Silvia; Toubes, María Elena; Álvarez-Dobaño, José Manuel; Valdés, Luis
ABSTRACT: Introduction : The management of infected pleural effusion is complex. Therapeutic resolution requires determining the following: appropriate antibiotic regimen, the need for pleural drainage, the optimal drainage tube size, and the need for intrapleural therapy or surgery. Areas covered : An updating of the latest advances in the management of parapneumonic pleural effusion based on the best evidence available is provided. Expert commentary : The correct management of parapneumonic pleural effusion is based on selecting an antibiotic regimen according to the origin of the pleural infection (community-acquired or nosocomial). If pleural drainage is indicated, a small-bore chest tube is appropriate. Although the administration of fibrinolytics is not required in all cases, when necessary, recombinant t-PA in combination with deoxyribonuclease is the preferred therapy. If surgery is indicated, video-assisted thoracoscopic surgery is as effective – if not superior – as open decortication. All these therapies should be complemented with appropriate nutritional support. Further clinical trials are needed to confirm whether new therapeutic strategies such as a pleural cavity saline wash are more effective in the management of this disease.